Libraries, archives, and museums in transition : changes, challenges, and convergence in a Scandinavian perspective - Rasmussen, Casper Hvenegaard, 1967-; Rydbeck, Kerstin; Larsen, Hakon (London ; New York, New York : Routledge, 2023)
"In this anthology, top scholars researching libraries, archives, and museums (LAM) issues in Scandinavia explore pressing issues for contemporary LAMs. In recent decades, relations between libraries, archives, and museums (LAMs) have changed rapidly: collections have been digitized, books, documents and objects have been mixed in new ways, and LAMs have picked up new tasks in response to external changes. Libraries now host makerspaces and literary workshops, archives fight climate change and support indigenous people, and museums are used as instruments for economic growth and urban planning. At first glance, the described changes may appear as a divergent development, where the LAMs are growing apart. However, this book demonstrates that the present transformation of LAMs is primarily a convergent development. Libraries, Archives, and Museums in Transition will be essential reading for students and scholars and practitioners seeking to get on top of the LAM literature and the particularities of Scandinavian LAMs"-- Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Collection management (Libraries); Museums -- Collection management; Electronic books